2007
DOI: 10.1002/ange.200700891
|View full text |Cite
|
Sign up to set email alerts
|

Helical Arrangement of Interstrand Stacked Pyrenes in a DNA Framework

Abstract: Zusammengebracht: Die Selbstorganisation von Oligopyrensträngen mit 14 aufeinander folgenden achiralen Pyrenbausteinen in einem DNA‐Strang liefert eine künstliche Doppelhelix (siehe Bild, Oligopyrenregionen in dunklen, flankierende DNA‐Regionen in hellen Farben). Die Helizität der Oligopyrenabschnitte wird durch Excitonen‐gekoppelte CD‐Signale der Pyreneinheiten eindeutig belegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 66 publications
1
35
0
5
Order By: Relevance
“…[64] Die bestimmten Energien für die beiden Waagentypen, 5 mit einem unsubstituierten und 6 mit einem CF 3 [65] auf Basis eines einfachen elektrostatischen Solvatisierungmodells. [66] Insgesamt sind die beobachteten Substituenteneffekte in guter Übereinstimmung mit den oben besprochenen Ergebnissen der Rechnungen von Kim,…”
Section: Modellstudienunclassified
“…[64] Die bestimmten Energien für die beiden Waagentypen, 5 mit einem unsubstituierten und 6 mit einem CF 3 [65] auf Basis eines einfachen elektrostatischen Solvatisierungmodells. [66] Insgesamt sind die beobachteten Substituenteneffekte in guter Übereinstimmung mit den oben besprochenen Ergebnissen der Rechnungen von Kim,…”
Section: Modellstudienunclassified
“…For example, nucleobases have been successfully exploited in the creation of a variety of supramolecular nanostructures of different chromophores, such as porphyrin, [9] pyrene, [10] thiophene, [11] anthracene, [12] oligo(p-phenylenevinylene)s [13] and other small organic molecules. [14] Similarly, DNA has also been used as the structural scaffold for the helical organization of a series of chromophores including pyrene, [15][16][17][18][19] porphyrin, [20] biphenyl, [21] oligo(p-phenylenevinylene)s [22] etc. and dyes including azobenzene derived dyes, [23] perylene bisimide [24][25][26] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[15] It has also been reported that the shift of the excimer emission band can be used as a signal to detect hybridization, as the excimer fluorescence could redshift or blue-shift upon hybridization by the interstrandstacked pyrenes. [16] Although both monomer and excimer emission of pyrene-labeled probes has been investigated in detail, the often complex response depends on the structure of the probe.…”
Section: Introductionmentioning
confidence: 99%